Biodiversity of Costus speciosus Phylloplane Fungi in Baturaden Botanical Gardens and Antagonist Testing against Fusarium oxysporum - Aulia, Muhammad Hilman; Rukmi, Isworo; Suprihadi, Agung; Mahardhika, Wahyu Aji (Universitas Negeri Surabaya, 2024)
Indonesia has an abundant biodiversity of natural resources, one of which is phylloplane fungi. This abundant phylloplane mold needs further investigation to utilize its potential as an antagonistic agent. This study aims to prove the existence and to determine the types of phylloplane fungi species found on the leaf surface of pacing tawar (sweet ginger or crepe-ginger) plants, to analyze and determine the level of diversity and dominance of phylloplane, and to determine the types of phylloplane fungi species that have the antagonistic ability of the phytopathogenic mold Fusarium oxysporum. This research method includes isolating crepe-ginger phylloplane fungi using a contact plate, isolates purification, macromorphological and micromorphological identification, diversity and dominance index calculation, and antagonist test using a dual culture method. This study used a descriptive analysis research design. The isolation results obtained 57 species of crepe-ginger plants leaf phylloplane molds consisting of eight genera (Alternaria, Aspergillus, Cladosporium, Curvularia, Fusarium, Mucor, Penicillium, and Trichoderma). The results of the diversity index calculation with a value of 2.02 showed that the diversity of phylloplane fungi was moderate. The result of the dominance index calculation, with a value of 0.1521, shows no tendency for phylloplane fungi species to dominate. The results of the antagonist test showed that 15 isolates could antagonize the F. oxysporum with an inhibitory proportion of up to 82% obtained from T. viride isolates with code FD5B3.2